Au-delà de la relation « bourreau-victime » dans l’analyse d’une situation de harcèlement psychologique au travail - Michel Vézina; Julie Dussault (Perspectives Interdisciplinaires sur le Travail et la Santé)
Legislation has been adopted in several countries to counter psychological harassment in the workplace. Even if it is often necessary, from a legal standpoint, that the means involve the personal protection of victims, more than a person-centred approach must be considered for stopping this wrong. Also, beyond a « bully-victim » approach, in the short view, real prevention of workplace psychological harassment is achieved by analyzing and eliminating organizational factors and cultural aspects that constitute a fertile breeding ground for the emergence of violent behaviours between members of the same work organization. These factors are mainly intensification of the work, weakness of the hierarchical authority, precariousness of the ties to employment, as well as the banalization or negation of the phenomenon, tolerance of incivility, and iniquity or injustice in the workplace. Like the fault tree used in investigating an occupational accident, professionals faced with a psychological harassment situation are encouraged to adopt an approach that goes beyond the initial findings, to deal with the more indirect causes of the phenomenon, namely deficiencies in the management system.